Seismic imaging of the shallow crust beneath the Krafla central volcano, NE Iceland. Issue 10 (30th October 2015) - Schuler, Juerg; Greenfield, Tim; White, Robert S.; Roecker, Steven W.; Brandsdóttir, Bryndís; Stock, Joann M.; Tarasewicz, Jon; Martens, Hilary R.; Pugh, David
Abstract: We studied the seismic velocity structure beneath the Krafla central volcano, NE Iceland, by performing 3‐D tomographic inversions of 1453 earthquakes recorded by a temporary local seismic network between 2009 and 2012. The seismicity is concentrated primarily around the Leirhnjúkur geothermal field near the center of the Krafla caldera. To obtain robust velocity models, we incorporated active seismic data from previous surveys. The Krafla central volcano has a relatively complex velocity structure with higher P wave velocities ( V p ) underneath regions of higher topographic relief and two distinct low‐ V p anomalies beneath the Leirhnjúkur geothermal field. The latter match well with two attenuating bodies inferred from S wave shadows during the Krafla rifting episode of 1974–1985. Within the Leirhnjúkur geothermalreservoir, we resolved a shallow (−0.5 to 0.5 km below sea level; bsl) region with low‐ V p / V s values and a deeper (0.5–1.5 km bsl) high‐ V p / V s zone. We interpret the difference in the velocity ratios of the two zones to be caused by higher rock porosities and crack densities in the shallow region and lower porosities and crack densities in the deeper region. A strong low‐ V p / V s anomaly underlies these zones, where a superheated steam zone within felsic rock overlies rhyolitic melt. Key Points: We performed a seismic tomography of the Krafla caldera using earthquake and active seismic data A low‐ V p / V s zone was imaged beneath the depth where boreholes drilled into rhyolitic magma A low‐ V p / V s zone overlies a high‐ V p / V s zone likely caused by changes in lithology